Ghosts of war : Nazi occupation and its aftermath in Soviet Belarus - Exeler, Franziska (Cornell University Press, 2022)
"Focusing on Belarus, an East European borderland and Soviet republic that was particularly affected by the Second World War, the book investigates the choices that the local population made (and was forced to make) under Nazi occupation, and examines their political, social, legal, and personal repercussions in the postwar decades."